The CHILES Continuum and Polarization Survey. I. Survey Design and Noise Characterization - Nicholas M. Luber; Min S. Yun; Hansung B. Gim; Daniel Krista-Kelsey; D.J. Pisano; Emmanuel Momjian; Chris Hales (The Astronomical Journal, 2025)
We introduce and describe the CHILES Continuum and Polarisation (CHILES Con Pol) Survey, a 1000 hr 1.4 GHz wideband full polarization radio continuum deepfield with the Very Large Array, commensurate with the CHILES H i deepfield. We describe the observational configuration, outline the calibration of the data, and discuss the effect of radio frequency interference on different observing epochs. In addition, we present a novel radio continuum imaging strategy, using well-known baseline subtraction techniques in radio spectral data, and discuss the applications to the removal of artifacts from sources far from the field center. Additionally, we discuss the nature of a low-level image-wide offset, the so-called “negative bowl,” and simulate our observations in order that we may both properly understand and correct for this artifact. Using these techniques, we present the first total intensity image of the data which achieves an rms noise of 1.3 μ Jy beam ^−1 with a synthesized beam of 4 $\mathop{.}\limits^{\unicode{x02033}}$ 5 × 4 $\mathop{.}\limits^{\unicode{x02033}}$ 0, the most sensitive L -band image ever taken at this resolution. We then place this image into the broader context of 1.4 GHz radio continuum surveys in the literature, in terms of image sensitivity and fidelity, and μ Jy level source counts and P ( D ) analysis.